Pre-stress performance in an instrumental training predicts post-stress behavioral alterations in chronically stressed rats - Iguchi, Yoshio; Kosugi, Sakurako; Lin, Ziqiao; Nishikawa, Hiromi; Minabe, Yoshio; Toda, Shigenobu (Frontiers in Behavioral Neuroscience, 2015)
Stress is a major factor in the development of major depressive disorder (MDD), but few studies have assessed individual risk based on pre-stress behavioral and cognitive traits. To address this issue, we employed appetitive instrumental lever pressing with a progressive ratio (PR) schedule to assess these traits in experimentally naïve Sprague-Dawley rats. Based on four distinct traits that were identified by hierarchical cluster analysis, the animals were classified into the corresponding four subgroups (Low Motivation, Quick Learner, Slow Learner, and Hypermotivation), and exposed to chronic unpredictable stress (CUS) before monitoring their post-stress responses for 4 weeks. The four subgroups represented the following distinct behavioral phenotypes after CUS: the Low Motivation subgroup demonstrated weight loss and a late-developing paradoxical enhancement in PR performance that may be related to inappropriate decision-making in human MDD. The Quick Learner subgroup exhibited a transient loss of motivation and the habituation of serum corticosterone (CORT) response to repeated stress. The Slow Learner subgroup displayed resistance to demotivation and a suppressed CORT response to acute stress. Finally, the Hypermotivation subgroup exhibited resistance to weight loss, habituated CORT response to an acute stress, and a long-lasting amotivation. Overall, we identified causal relationships between pre-stress traits in the performance of the instrumental training and post-stress phenotypes in each subgroup. In addition, many of the CUS-induced phenotypes in rats corresponded to or had putative relationships with representative symptoms in human MDD. We concluded that the consequences of stress may be predictable before stress exposure by determining the pre-stress behavioral or cognitive traits of each individual in rats.